CORRELATION BETWEEN SOLAR CYCLES AND DUST ACTIVITY OVER IRAQ - Mohammed, Bashair Abdul-Rahaman (Al-Nahrain Journal of Science, 2010)
This work presents the results of statistical analysis of observed and severe dust visibility in Iraqin relation to the sunspot cycle for the periods 1959-2007 for Baghdad, 1978-2001 for Rutbah and1987-2007 for Mousl, Nasiriyah and Basrah. Examination of each dust series was subjected to timeand spectral analysis based on lag correlation. The result shows presence of a significant dust cyclesimilar to the sunspot cycle. The cross-correlation between the dust and air temperature with thesunspot activity shows a high correlation with the 11year sunspot cycle. Moreover, Fast FourierTransformation spectral analysis for the dust series confirms the similarity agreement to the sunspotvariations.